Pengembangan Ensiklopedia Tanaman Obat Berbasis Potensi Lokal di Kota Subulussalam sebagai Sumber Belajar Materi Plantae - Solin, Raslina; Febriani, Husnarika; Rohani, Rohani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This study aims to determine the development of an encyclopedia of medicinal plants in the City of Subulussalam and the feasibility of an encyclopedia of medicinal plants in the City of Subulussalam as a source of learning material for class X plant diversity. The research method was used the Research and Development (R&D) research method with the Borg and gall development model which has been modified to 8 steps from 10 steps that should be, namely 1) Potential problems, 2) Data collection, 3) Product design, 4) Product validation, 5) Design revision, 6) Product validation, 7) Product revision, and 8) Final product with media feasibility conclusion. Based on the results of the validation analysis by material expert validators, media experts, and biology teacher, it is known that the results of material expert validation have a percentage of 97.22%, media expert validation has a percentage of 100%, and validation by biology teacher has a percentage of 98.21%, it can be concluded from the three validation results by biology lecturers and teacher that they can be categorized into very suitable criteria for use as a learning resource. In a field trial with a limited scope and a wider scope, it is known that the results of a limited scope trial have a percentage of 91%, and a wider field trial has a percentage of 96.67%, it shows that the encyclopedia of medicinal plants is very suitable to be used as a learning resource for participants educate. Keywords: Encyclopedia, Plantae, Local Potential.